Error Analysis on Efl Students’ Essay Writing (Fourth Semester Students of STMIK Sinar Nusantara Surakarta) - Suryanti Galuh Pravitasari (Faculty of Language and Literature, University of Surakarta, 2022)
This research was finding out the errors made by English Foreign Language students in the essay writing using James’ error analysis. This study was qualitative descriptive research with 30 respondents. The data were collected by students’ mini research report which was then analyzed by observation and classification using Corder’s algorithm. It basically consists of three major stages: recognition, description, and explanation. Finally, the result was classified by using James’ four grammatical error categories. It was found out that there were 200 (100%) grammatical errors containing omission as many as 51 errors (25.5%), addition as many as 18 errors (9%), misformation as many as 105 errors (52.5%), and misordering as many as 26 errors (13%). An error correction activity was also conducted in order to decrease the errors. The result after the treatment was quite significant in which the total number of grammatical errors was decreasing from 200 to 92 containing Omission (22.9%), Addition (8.7%), Misformation (60.8%), and Misordering (7.6%). The main causes of the errors are the lack of the students’ understanding on the target language’s grammar rules and their tendency of using their first language’s grammar rules.